OPINIONS AND ATTITUDES OF CONSUMERS RELATED TO THE PURCHASE OF POTATOES AND REPERCUSSION ON THE OFFER OF FRENCH CULTIVARS - RIBEIRO, RITA DE CÁSSIA; SANT’ANA, HELENA MARIA PINHEIRO; DE PÁDUA, JOAQUIM GONÇALVES; CHAVES, JOSÉ BENÍCIO PAES (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2013)
ARTIGO RITA DE CÁSSIA